Internal structure parameters and synthesis conditions of polycrystalline diamond films - Samsonenko, S.N.; Samsonenko, N.D.; Kolupaeva, Z.I. (Functional Materials, 2007)
The dependence of the internal structure parameters of polycrystalline diamond films on their thickness that is a function of the synthesis duration at the specified temperature has been studied. It has been established that the block size and the film micro-distortions are reduced at the temperature 1073 K and the gas mixture pressures of 10.6 and 21.3 kPa. The dislocation density remains almost unchanged when passing from "thin" films (4-6 μm) to "thick" ones (10-12 μm). At the temperature 1173 K and gas mixture pressures 10.6 and 21.3 kPa, the block size diminishes and micro-distortions increase when the film thickness rises. The dislocation density increases in this case. These two polycrystalline diamond films synthesis regimes are of good prospects for study of the polycrystalline diamond films electron properties formation, since the dislocations give rise to electrical active centers in diamond materials. The recrystallization of the polycrystalline diamond films crystallites starts at 1273 K and pressures of 10.6, 21.3, 31.9 kPa or at pressure 31.9 kPa and synthesis temperatures 1073 K, 1173 K, 1273 K. That effect hinders the control dislocation density control.